From 'traitors' to 'saviours': A longitudinal analysis of Ethiopian, Kenyan and Rwandan embassies' practice of digital diaspora diplomacy. Issue 3 (3rd July 2021) - Manor, Ilan; Adiku, Geraldine Asiwome
ABSTRACT: Recent years have seen the emergence of relational approaches to diplomacy that centre on diplomats' use of social media to foster relationships with foreign publics. Yet social media may also prove useful in building relationships with diasporas, now viewed by some states as 'saviours' who may contribute to the economic prosperity of origin countries. This article sought to examine how Ethiopian, Kenyan and Rwandan embassies employ social media when communicating with diasporas. The article proposes a conceptual framework for digital diaspora diplomacy which consists of relationship building, community strengthening and relationship leveraging. An analysis of 830 Facebook posts, published in 2016 and 2020, suggests that evaluated embassies use social media to interact with Facebook followers, respond to online criticism, publicise offline events and publish information that is of interest to diasporas. Thus, African embassies may be able to leverage diasporic ties towards the improvement of their nation's socio-economic status.